The oral Pilipino vocabulary of Pampango-speaking grade one entrants of West Arayat district - Balingit, Purificacion Calma- 1931- (1973)
The writer believes that a word list in Pilipino for the major linguistic groups in the country will be useful in the preparation of the needed textbooks and other instructional materials in Pilipino. This study was specifically concerned with Pampango-speaking grade one entrants. The subjects were 60 Grade one entrants who have not had any formal training or instruction in Filipino and who speak only Pampango at home. Selected pictures from the Philippine Language Series for Grades I-IV were used to elicit responses in Pilipino. The study revealed that the girls have a larger vocabulary than the boys.However, additional data should be gathered using bigger sample to get a more accurate, comprehensive and conclusive evidence on the oral Pilipino vocabulary of Pampango-speaking grade one entrants.
Thesis (M.A. Teaching : Reading)--University of the Philippines, Diliman.
Keywords: Filipino language -- Study and teaching (Primary) -- Pampango speakers; Filipino language -- Vocabulary; First grade (Education) -- Philippines -- Arayat (Pampanga).